Pengaruh Model Pembelajan Team Games Tournament (TGT) Terhadap Hasil Belajar IPA Kelas VIII SMPN Satap Dotte Kabupaten Halmahera Tengah Pada Konsep Pesawat Sederhana - Daniati, Nia; Rifai, Rusni R (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2024)
This research is an experimental study aimed at determining whether the use of the Team Games Tournament (TGT) learning model affects the physics learning outcomes of eighth-grade students at SMPN Satap Dotte, Central Halmahera Regency, on the concept of Simple Machines. It also aims to determine the extent of the improvement in physics learning outcomes of eighth-grade students at SMP Negeri Satap, Central Halmahera Regency, using the game-based learning model (TGT) on the concept of Simple Machines for the 2023-2024 academic year. The study consists of one classroom with 26 students, divided into two groups for the experimental and control classes. This type of research is a quasi-experimental study using a nonequivalent control group design and purposive sampling technique. The sample used consists of 13 students in the experimental class and 13 students in the control class. The instrument used is a test instrument in the form of an objective multiple-choice test consisting of 20 questions with a score range of 0-1. The results of this study were tested statistically using the IBM SPSS version 26 "t" test application program. Based on the calculations, the obtained t-value was 3.713, while the t-table value was 2.064. According to the acceptance criteria, it was found that t-value > t-table at a significance level of 0.05 for the posttest data. According to the hypothesis test, it can be concluded that there is an influence and improvement of the tournament games-based learning model on students' physics learning outcomes regarding the concept of simple machines.